Finding of experience of the use of computer-integrated forms and methods of teaching in the process of preparation of future teachers of initial school - Sinopalnikova N.N (Kharkov National Pedagogical University, 2010)
Theoretically grounded and experimentally examined that one of the trends of future teachers training for the integrated activity is gaining experience in using the integrated organization forms of learning. It is realized in the process of specially organized student's learning and during their pedagogical practice. It was promoted by conducting the special course The integrated forms of learning organization in primary school with the use of interactive forms and methods of learning, fulfilling the aimed tasks while passing pedagogical practice.